Cr/ITO semi-transparent n-type electrode for high-efficiency AlGaN/InGaN-based near ultraviolet light-emitting diodes. (November 2017) - Kim, Hwankyo; Kim, Dae-Hyun; Seong, Tae-Yeon
Abstract: We investigated the electrical performance of near ultraviolet (NUV) (390 nm) light-emitting diodes (LEDs) fabricated with various semi-transparent Cr/ITO n -type contacts. It was shown that after annealing at 400 °C, Cr/ITO (10 nm/40 nm) contact was ohmic with a specific contact resistance of 9.8 × 10 −4 Ωcm 2 . NUV AlGaN-based LEDs fabricated with different Cr/ITO (6–12 nm/40 nm) electrodes exhibited forward-bias voltages of 3.27–3.30 V at an injection current of 20 mA, which are similar to that of reference LED with Cr/Ni/Au (20 nm/25 nm/200 nm) electrode (3.29 V). The LEDs with the Cr/ITO electrodes gave series resistances of 10.69–11.98 Ω, while the series resistance is 10.84 Ohm for the reference LED. The transmittance of the Cr/ITO samples significantly improved when annealed at 400 °C. The transmittance (25.8–45.2% at 390 nm) of the annealed samples decreased with increasing Cr layer thickness. The LEDs with the Cr/ITO electrodes exhibited higher light output power than reference LED (with Cr/Ni/Au electrode). In particular, the LED with the Cr/ITO (12 nm/40 nm) electrode showed 9.3% higher light output power at 100 mA than reference LED. Based on the X-ray photoemission spectroscopy (XPS) and electrical results, the ohmic formation mechanism is described and discussed. Highlights: We investigated the performance of NUV LEDs with various semi-transparent Cr/ITO contacts. LEDs with Cr/ITO contacts exhibited forward voltages similar to that of reference LEDs. LEDs with the Cr/ITO contacts showed higher light output power than reference LEDs. Ohmic formation was attributed to reduced Schottky barrier heights due to the outdiffusion of N vacancies.